2020 International Conference on ICT for Smart Society (ICISS) 2020
DOI: 10.1109/iciss50791.2020.9307558
|View full text |Cite
|
Sign up to set email alerts
|

Developing Distance Learning Monitoring Dashboard with Google Sheet: An Approach for Flexible and Low-Price Solution in Pandemic Era

Abstract: The Covid-19 pandemic has prompted many colleges and students to conduct distance learning (PJJ), unprepared. Thus, it is necessary to carry out continuous evaluation and improvement in a faster period, monthly or weekly. Therefore, an approach is needed to help the campus stay on track, and still maintain the quality of learning. It is performance monitoring. However, building a monitoring dashboard requires many resources. This study proposes a design solution using Google Sheet, which is flexible, easy to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
1
3
0
2
Order By: Relevance
“…During COVID-19 pandemic, empirical studies have shown that poor quality Internet access and less digital literacy skills were associated with lower use of the Internet for educational purposes (Van Deursen, 2020). Similarly, in the current review, we reported students' digital inequalities to properly access learning content and lack of digital skills to utilize online environments as two important challenges (e.g., Günther, 2021;Rahmah et al, 2020).…”
Section: Online Distance Education Challenges (Rq1)supporting
confidence: 65%
See 1 more Smart Citation
“…During COVID-19 pandemic, empirical studies have shown that poor quality Internet access and less digital literacy skills were associated with lower use of the Internet for educational purposes (Van Deursen, 2020). Similarly, in the current review, we reported students' digital inequalities to properly access learning content and lack of digital skills to utilize online environments as two important challenges (e.g., Günther, 2021;Rahmah et al, 2020).…”
Section: Online Distance Education Challenges (Rq1)supporting
confidence: 65%
“…For instructors, this may be due to the decreased chance/opportunity for real time monitoring of learners. Similar to students, higher education instructors were not ready for online learning; therefore, we found that instructors were far from delivering best quality online lecture pedagogically and technically (e.g., Rahmah et al, 2020).…”
Section: Online Distance Education Challenges (Rq1)mentioning
confidence: 89%
“…Hence, an open-source software -Google Sheets was utilized. Google Sheets is an opensource cloud-based online application that allows working with other people in unison [14,15]. The application helps in creating and formatting spreadsheet documents in cloud space using the internet [16,17].…”
Section: Methodsmentioning
confidence: 99%
“…Sistem monitoring berbasis Google Sheets telah dilakukan pada berbagai jenis perangkat IoT [15], [16], [17]. Dengan menggunakan media Google Sheets, monitoring akan lebih mudah dan dapat dipahami secara umum karena dapat diatur seperti menggunakan program Microsoft Excel yang didalamnya sudah memiliki sistem komputasi dasar yang cukup familiar [18], [19], [20].…”
Section: Pendahuluanunclassified